ANALYSIS OF INFILTRATION RELATIONS WITH LAND PHYSICAL PROPERTIES - Awliya Tribhuwana; Agung Prasetyo (Journal of Green Science and Technology, 2020)
ABSTRACTSoil types have different infiltration rates and vary depending on the characteristics of the soil, how the infiltration relationship occurs with dry water content and saturated water content, infiltration relationship with the soil after being compacted and before compacted and how the infiltration rate of the two types of relationship and how infiltration water that happened. Soil tests are carried out in the laboratory, soil water content before and after the soil has been solidified, changes in the time of infiltration capacity with the Horton equation, rain hydrograph for overall infiltration analysis, including cumulative infiltration and runoff rates.Soils experience porosity filling not as great as in normal soil conditions, normal soil conditions changes in water content reaches 5.22 mm/hour while in soil conditions that experience changes in water content compaction at 30 minutes by 0.14 mm/hour and experiences a constant rate in the 40th minute at a rate of 0.20 mm/hour, so there is a difference in water content of 5.08 mm/hour between normal soil and soil after solidification, due to compacting it causes runoff of 8.92 mm/hour, normal soil with runoff of 3.78 mm/hour.Keyword :  Infiltration, soil physical properties, runoff.